2007
DOI: 10.1124/jpet.107.119800
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Novel Imidazole-Dioxolane Heme Oxygenase Inhibitors in Renal Proximal Tubule Epithelial Cells

Abstract: To enhance our understanding of the physiological roles of heme oxygenase (HO) isozymes, HO-1 (inducible) and HO-2 (constitutive), we developed novel imidazole-based HO inhibitors. Unlike the metalloporphyrins, these imidazole-dioxolane compounds are selective for the in vitro inhibition of HO with minimal effects on other heme-dependent enzymes such as nitric oxide synthase and soluble guanylyl cyclase. In the current study, we tested the hypothesis that these novel HO inhibitors are effective in intact cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…The H chain of ferritin demonstrates high ferroxidase activity inhibiting the redox cycling of iron [21] thus reducing the risk of oxidative stress related to iron oxidation and favoring the cytoprotective effect of heme oxygenase-1 [22,23]. Heme oxygenase-1 deficient mice demonstrated increased sensitivity to heme-containing proteins -mice in the rhabdomyolysis model demonstrated substantially higher levels of blood creatinine and lactate dehydrogenase and an increased death rate while inhibition of heme oxygenase-1 in situ caused heme-induced apoptosis of kidney cells [24]. Myoglobin detoxication depends not only on its proteolytic degradation but also on how active is the subsequent heme and iron degradation system.…”
Section: Discussionmentioning
confidence: 99%
“…The H chain of ferritin demonstrates high ferroxidase activity inhibiting the redox cycling of iron [21] thus reducing the risk of oxidative stress related to iron oxidation and favoring the cytoprotective effect of heme oxygenase-1 [22,23]. Heme oxygenase-1 deficient mice demonstrated increased sensitivity to heme-containing proteins -mice in the rhabdomyolysis model demonstrated substantially higher levels of blood creatinine and lactate dehydrogenase and an increased death rate while inhibition of heme oxygenase-1 in situ caused heme-induced apoptosis of kidney cells [24]. Myoglobin detoxication depends not only on its proteolytic degradation but also on how active is the subsequent heme and iron degradation system.…”
Section: Discussionmentioning
confidence: 99%
“…The study focused on the systematic design and synthesis of analogs of QC-1, which were screened by an in vitro CO-formation assay using microsomal samples derived from rat spleen and brain as the physiological sources of HO-1 and HO-2, respectively. Moreover, analyses on the in vivo efficacy of some select compounds have also been performed in mice and rats (Dercho et al, unpublished results), as well as in cultured cells [30]. This program has led to a series of novel compounds, which do not affect NOS or sGC except at high millimolar concentrations, nor do they induce expression of NOS, sGC, or HO-1.…”
Section: Introductionmentioning
confidence: 97%
“…Zinc-protoporphyrin was developed to treat cancer (Fang et al, 2004b). Recently, imidazole-dioxolane compounds have been shown to act as inhibitors of HO activity (Vlahakis et al, 2006;Sugishima et al, 2007) and shown to be effective as inhibitors of specific HO isoenzymes as well as HO activity (Kinobe et al, 2007).…”
Section: B Heme Oxygenase Isozymesmentioning
confidence: 99%